Anglo-Indian education : a study of its origins and growth in Bengal up to 1960 - D'Souza, Austin Anthony (Delhi : Oxford University Press, 1976)
S. Muthiah traces the origins and growth of four generations of Anglo-Indians, combining meticulous research and a descriptive-analytical approach enlivened by personal anecdote and imagery.
Bibliography: p. 333-338.
Keywords: Education -- History -- India -- Bengal; Schools, British -- India -- Bengal